Курганы бассейна Мокрой Волновахи (северо-восточное Приазовье) - Привалова, О.Я. (Археологический альманах, 2004)
In 1976, in the river Mokra Volnovakha basin (Volnovakha district of the Donetsk region) four barrows were excavated. Two barrows were excavated near the Nikolayevka settlement of the Timber-Grave Culture. Two burials of the Pit Culture (No 2 in the barrow No 1, No 12 in the barrow No 2), one burial of the Catakomb Culture (No 2 in the barrow No 2), two burials of the Babino Culture (No 1,11 in the barrow No 2), eight burials of the Timber-Grave Culture (No 1 in the barrow No 1, No 3-9 in the barrow No 2) and one burial of Middle Age nomads (No 10 in the barrow No 2) were investigated in these barrows. Two barrows were excavated in the group “Maly Kut” (barrow No 2 was published already). One burial of the Pit Culture (No 5) and three burials of the Timber-Grave Culture (No 1-3) were investigated in barrow No 1.